The Effects of YouTube Home Training Content Characteristics, Personal Health Awareness, and Exercise Awareness on Intention to Exercise Continuous Intention Using the Expectation-Confirmation Model - Hyungchul Joo (Korea Institute of Sport Science, 2022)
PURPOSE Since the COVID-19 pandemic, the demand for home training, with exercises or workouts at home, has steadily increased. As a result, the popularity of home training YouTube content, which shows how to use exercise equipment or workouts without professional influence, has also increased. Therefore, this study focused on the characteristics of YouTube home training content (specialization, diversity, and interaction), personal health awareness, exercise awareness, and expectation-confirmation model to identify which required exercise continuation intention through YouTube home training. METHODS SPSS and AMOS software were used to conduct frequency, reliability, and confirmatory factor analyses, as well as to conduct correlation analysis and construct a structural equation model. RESULTS First, health and exercise awareness had a positive effect on confirmation. Second, among the characteristics of home training content, only specialization had a positive effect on perceived usefulness. Third, confirmation had a positive effect on perceived usefulness and viewing satisfaction, perceived usefulness had a positive effect on viewing satisfaction and exercise continuation intention, and viewing satisfaction had a positive effect on exercise continuation intention, which proved the expectation-confirmation model in this study. CONCLUSIONS To increase exercise continuation intention through home training YouTube content, creators need to produce professional content that can stimulate viewers' internal motivation.